بحوث العلوم الاجتماعية والإنسانية المدعومة من هيئة أبحاث العلوم الطبيعية والتكنولوجيا – ليبيا 2009- 2018 " الواقع والآفاق المستقبلية" - حسين سالم مرجين (Scientific Journal of University of Benghazi, 2018)
This paper seeks to identify the reality of research in social and human sciences, backed by science and technology research in Libya, in addition to knowing the most important barriers to science and technology research support operations and continue research in social sciences And humanity, it also aims to identify the main tracks for access towards research strategy to social and human sciences, and science and technology research on characterization of research in the social sciences and Humanities that has a social function seek to serve And development of society and its development and increase its productivity, achieving safe cultural, social, economic and political. Etc, in addition to providing scientific solutions to various problems, the paper concluded the most important results to the fact that community transformations known to Libyan society after 2011, become necessarily call for promoting and developing scientific research in the fields of social sciences and Humanities, in order to understand the most important The parameters of the processes and actors behind those transitions, add to search and detection of implicit and Orientalism, as developments called for a renewed